Association between obesity and sleep disorder in the elderly: evidence from NHANES 2005–2018 - Wang, Weifei; Chen, Zhong; Zhang, Wenyuan; Yuan, Rui; Sun, Yaqi; Yao, Qi; Lu, Jian; Zheng, Jungang (Frontiers in Nutrition, 2024)
Background: The available data exhibit inconsistent findings regarding the association between obesity and sleep problems among older adults. The objective of this study was to assess the potential association between obesity and sleep disorders in the older population. Methods: The data utilised in this cross-sectional investigation was obtained from the National Health and Nutritional Examination Survey (NHANES) conducted between 2005 and 2018. The study employed a multivariate logistic regression model and conducted subgroup analysis to evaluate the association between obesity and sleep disturbance. Results: The investigation consisted of 2,570 older people who provided complete information, out of which 324 individuals satisfied the criteria for sleep disturbance. The findings from the multivariable adjusted logistic regression model indicate that individuals in the overweight and normal weight groups exhibited decreased odds of experiencing sleep disorder, as evidenced by the adjusted odds ratios (AOR) of 0.46 (95% confidence interval [CI] = 0.34-0.61) and 0.33 (95% CI = 0.22-0.47), respectively. These results were statistically significant (P < 0.001) when compared to individuals in the obese group. The investigation of age and gender subgroups demonstrated similar associations between various BMI categories and sleep disorders in the older population. Conclusions: In summary, there exists a correlation between obesity and sleep disorders in the senior population. A significant association was observed between BMI and the likelihood of experiencing sleep disorders, indicating a dose-response relationship. Individuals with a higher BMI demonstrated a heightened likelihood of experiencing sleep disorders compared to those with a lower BMI.